Imagined motor action and eye movements in schizophrenia - Delerue, Céline; Boucart, Muriel (Frontiers in Psychology, 2013)
Visual exploration and planning of actions are reported to be abnormal in schizophrenia. Most of the studies monitoring eye movements in patients with schizophrenia have been performed under free-viewing condition. The present study was designed to assess whether mentally performing an action modulates the visuomotor behavior in patients with schizophrenia and in healthy controls. Visual scan paths were monitored in eighteen patients with schizophrenia and in eighteen healthy controls. Participants performed two tasks in which they were asked either to (1) look at a scene on a computer screen (free viewing), or (2) picture themselves making a sandwich in front of a computer screen (active viewing). The scenes contained both task-relevant and task-irrelevant objects. Temporal and spatial characteristics of scan paths were compared for each group and each task. The results indicate that patients with schizophrenia exhibited longer fixation durations, and fewer fixations, than healthy controls in the free viewing condition. The patients’ visual exploration improved in the active viewing condition. However, patients looked less at task-relevant objects and looked more at distractors than controls in the active viewing condition in which they were asked to picture themselves making a sandwich in moving their eyes to task-relevant objects on an image. These results are consistent with the literature on deficits in motor imagery in patients with schizophrenia and it extends the impairment to visual exploration in an action imagery task.